The Interpretation of Birrul Walidayn in Q.S. Al-Isra [17]: 24 (A Comparative Study of Tafsir Al-Azhar and Marah Labid) - Alimuddin, Muhammad Faqih; Rhain, Ainur (Universitas Muhammadiyah Surakarta, 2023)
Devotion to one's parents is a commendable character often referred to as Birrul Walidayn. Children's devotion to their parents will not always be commensurate with the sacrifices parents make for their children. Devotion to parents can be shown through good service, polite words, and devotion to both. In this era, we often see the phenomenon of children disobeying their parents, which, of course, is very contrary to what Allah SWT and the Prophet Muhammad commanded. This research aims to determine the interpretation of Birrul Walidain in QS Al-Isra [17] 23-24 according to Tafsir Al Azhar and Marah Labid, as well as compare the similarities and differences between the interpretation of Birrul Walidain between the two interpreters. This research is library research. The data sources used are primary and secondary data, primary data in the form of the Tafsir Al Azhar Book by Hamka, the Book of Tafsir Marah Labid by Syekh Muhammad Nawawi, and secondary data in the form of journals, theses, scientific articles, and books that support this discussion. The method used to analyze this writing is the muqaran method. Based on the data analysis, from the interpretation of QS Al Isra verse 24, Buya Hamka and Sheikh Muhammad Nawawi agree that a child must care for both parents patiently and sincerely, be humble towards them, and pray for them.